Incidence of canine perianal tumours: a retrospective study - Chandini.G.Ashok; Ravi Sundar George; Mohamed Shafiuzama; S. Hemalatha (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The perianal region of dogs contain multiple glands, some of which are unique to the area, namely the perianal or circumanal(hepatoid) glands, the anal sac glands and the anal glands (Moulton, 2008 ). Perianal (circumanal or hepatoid) glands are modified sebaceous glands present in the perianal skin (Gross et. al.,2008). These glands are unique non-secretory abortive sebaceous glands in dogs and marsupials, situated around the anus in a uniform circle up to 2 cm from the anal orifice and scattered areas on the prepuce, tail, hind legs and trunk.